A pillar of fire by night - Kratman, Tom (Kratman, Tom. Carrera, 2019)
"Carrera's held off his enemies and dealt the Zhong Empire a stinging defeat which has only made them angrier. Now, though, his adopted country of Balboa is under assault from the east, south, west, the air and from space. Now the Taurans have assaulted Balboa trapping Carrera's Fourth Corps, and overrunning and capturing a large portion of his artillery train. In space, the United Earth Peace Fleet has been spying and feeding intelligence to both the Zhong and the Taurans. It's beginning to look like the game is up for Carrera. But Carrera has been planning this war for 15 years. He certainly hopes his enemies think they're winning"--